Handbook of satellite applications - Pelton, Joseph N.; Madry, Scott; Camacho-Lara, Sergio (Springer, 2017)
The first edition of this ground breaking reference work was the most comprehensive reference source available about the key aspects of the satellite applications field. This updated second edition covers the technology, the markets, applications and regulations related to satellite telecommunications, broadcasting and networking--including civilian and military systems; precise satellite navigation and timing networks (i.e. GPS and others); remote sensing and meteorological satellite systems. Created under the auspices of the International Space University based in France, this brand new edition is now expanded to cover new innovative small satellite constellations, new commercial launching systems, innovation in military application satellites and their acquisition, updated appendices, a useful glossary and more.- Resumé vydavatel
Keywords: umělé družice; satelitní komunikace; meteorologické družice; artificial satellites; satellite communication; meteorological satellites; elektronické knihy; sborníky; electronic books; papers of several authors